Customized Structure Design and Functional Mechanism Analysis of Carbon Spheres for Advanced Lithium–Sulfur Batteries. Issue 8 (11th January 2022) - Kang, Junbao; Tian, Xiaohui; Yan, Chenzheng; Wei, Liying; Gao, Lu; Ju, Jingge; Zhao, Yixia; Deng, Nanping; Cheng, Bowen; Kang, Weimin
Abstract: Lithium–sulfur batteries (LSBs) are attracting much attention due to their high theoretical energy density and are considered to be the predominant competitors for next‐generation energy storage systems. The practical commercial application of LSBs is mainly hindered by the severe "shuttle effect" of the lithium polysulfides (LiPSs) and the serious damage of lithium dendrites. Various carbon materials with different characteristics have played an important role in overcoming the above‐mentioned problems. Carbon spheres (CSs) are extensively explored to enhance the performance of LSBs owing to their superior structures. The review presents the state‐of‐the‐art advances of CSs for advanced high‐energy LSBs, including their preparation strategies and applications in inhibiting the "shuttle effect" of the LiPSs and protecting lithium anodes. The unique restriction effect of CSs on LiPSs is explained from three working mechanisms: physical confinement, chemical interaction, and catalytic conversion. From the perspective of interfacial engineering and 3D structure designing, the protective effect of CSs on the lithium anode is also analyzed. Not only does this review article contain a summary of CSs in LSBs, but also future directions and prospects are discussed. The systematic discussions and suggested directions can enlighten thoughts in the reasonable design of CSs for LSBs in near future. Abstract : Carbon spheres play an important role in inhibiting the "shuttle effect" of lithium polysulfides and protecting the lithium anode in lithium–sulfur batteries. In the future, various carbon spheres prepared by novel strategies combining with emerging materials and advanced characterization technologies can shine light on the practical application of lithium–sulfur batteries.